SPREADING OF MASTITIS AND PECULIARITIES OF THE MAMMARY GLAND QUARTERS’ LESION IN COWS OF DIFFERENT BREEDS ON THE FARMS OF SUMY REGION - Baydevlyatov, Y. A.; Baydevlyatova, Y. V. (Scientific Progress & Innovations, 2019)
Over the past decade there has been a rapid transition to industrial methods of dairy and meat production. This in turn caused the need to increase the rates of animal reproduction. However, the successful reproduction of the herd and the growth of livestock productivity are significantly hampered by obstetricgynecological pathology, including diseases of the mammary gland in cows. Mastitis causes significant economic losses to livestock farming. The aim of our work was to study the frequency of the mammary gland separate quarters’ lesion because of clinical mastitis among cows of different breeds and to establish the dynamics of developing atrophy and induction in them as a result of the disease. The following research methods were used to determine the clinical forms of mastitis: examination, palpation of the mammary gland and visual assessment of the secretion. The diagnosis was confirmed using biochemical, cytological, and bacteriological methods. In addition, the habitus, body temperature, appetite, production performance, and physiological condition of cows were determined. Our research has established that among the cows of black-and-white, Simmental, and Holstein breeds, in most cases, regardless of the form, one-quarter lesion of the udder with clinical mastitis predominated (85.0 %, 66.4 % and 75.8 %, correspondingly), less frequently two-quarter udder lesion occurred (14.6 %, 32.8 % and 23.3 %), and three-quarter udder lesion was an exception (0.4 %, 0.8 % and 0.9 %, correspondingly. It should also be noted that inflammation occurred more frequently in the rear udder quarters among the cows of all studied breeds (49.1 %, 38.4 % and 48.8 %, correspondingly), and less often in the fore ones (35.9 %, 27.9 % and 26.9 %). The frequency of mastitis complications in the form of atrophy and induration depended on the level of animal productivity. So, udder quarters’ atrophy was recorded on average in 19.9% – 19.1 % of cows in the highly productive Simmental and Holstein breeds (5,0–5,5 thousand kg), correspondingly, induration was recorded in 8.7% and 6.6 % of animals. As to black-and-white breed with the productivity of 4.7 thousand kg, the percentage of cows with signs of atrophy and induration of the udder quarters was 14.4 % and 5.8 %, correspondingly.